Microwave-assisted synthesis and characterization of roselike and flower-like zinc oxide nanostructures - Anukorn Phuruangrat (2018)
Hexagonal zinc oxide was synthesized by 180 W, 20 min microwave heating of 1:5 and 1:12.5 mole ratios of zinc chloride and sodium hydroxide as starting materials in aqueous solution system. The products were characterized using X-ray diffraction (XRD), scanning and transmission electron microscopy (SEM, TEM), and Fourier transform infrared (FTIR) and Raman spectroscopy. Rose-like particles of nanoplates and flower-like particles of nanorods of hexagonal zinc oxide with optical phonon E 2 vibration mode at 440 cm -1, and the stretching modes of Zn-O at 426 and 565 cm -1 were detected.